2012
DOI: 10.1007/s00381-012-1956-9
|View full text |Cite
|
Sign up to set email alerts
|

Shunt survival rates by using the adjustable differential pressure valve combined with a gravitational unit (proGAV) in pediatric neurosurgery

Abstract: In a concept of avoiding chronic overdrainage by using the proGAV in hydrocephalic children, we observed a good rate of valve and shunt survival. Compared to previous reported series, we experienced the proGAV as a reliable tool for the treatment of pediatric hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 41 publications
4
25
0
1
Order By: Relevance
“…Complications such as orthostatic headaches or subdural effusions can arise as acute sequelae under these conditions, and require revision or adjustment of the shunt [4,20]. Slit-like ventricles with possible obstruction of the ventricular catheter, microcephaly, calvarial hyperostosis, or shunt-induced Chiari malformations are also possible complications following chronic CSF overdrainage, especially in pediatric hydrocephalus patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Complications such as orthostatic headaches or subdural effusions can arise as acute sequelae under these conditions, and require revision or adjustment of the shunt [4,20]. Slit-like ventricles with possible obstruction of the ventricular catheter, microcephaly, calvarial hyperostosis, or shunt-induced Chiari malformations are also possible complications following chronic CSF overdrainage, especially in pediatric hydrocephalus patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…After promising early results, the standard regimen was changed to include infant patients. 18,48 In the present study, we report the shunt and valve survival rates and the reasons for valve exchanges exclusively for the infant cohort. The retrospective investigation of revisions and complication rates in this young patient cohort shows limited shunt and valve survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the feasibility of using this shunt system in an infant population is demonstrated, which has similarly been shown for a general pediatric population. 20,43,48 The use of the gravitational unit of the system to try to counteract severe overdrainage is also well tolerated by infants. Clinical observation has shown that during long-term follow-up, signs and symptoms of overdrainage (e.g., decreased ventricular size on imaging, diminished development of head circumference, and headaches) may develop with the advancing growth and activity of the child.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations